Cytoprotective and Neurotrophic Effects of Octadecaneuropeptide (ODN) in in vitro and in vivo Models of Neurodegenerative Diseases - Masmoudi-Kouki, Olfa; Namsi, Amira; Hamdi, Yosra; Bahdoudi, Seyma; Ghouili, Ikram; Chuquet, Julien; Leprince, Jérôme; Lefranc, Benjamin; Ghrairi, Taoufik; Tonon, Marie-Christine; Lizard, Gérard; Vaudry, David (Frontiers in Endocrinology, 2020)
Octadecaneuropeptide (ODN) and its precursor diazepam-binding inhibitor (DBI) are peptides belonging to the family of endozepines. Endozepines are exclusively produced by astroglial cells in the central nervous system of mammals and their release is regulated by stress signals and neuroactives compounds. There is now compelling evidence that the gliopeptide ODN protects cultured neurons and astrocytes from apoptotic cell death induced by various neurotoxic agents. In vivo, ODN causes a very strong neuroprotective action against neuronal degeneration in a mouse model of Parkinson’s disease. The neuroprotective activity of ODN is based on its capacity to reduce inflammation, apoptosis and oxidative stress. The protective effects of ODN are mediated through its metabotropic receptor. This receptor activates a transduction cascade of second messengers to stimulate PKA, PKC and MAPK-ERKs signaling pathways, which in turn inhibits the expression of pro-apoptotic factor Bax and the mitochondrial apoptotic pathway. In N2a cells, ODN also promotes survival and stimulates neurite outgrowth. During the ODN-induced neuronal differentiation process, numerous mitochondria and peroxisomes are identified in the neurites and an increase in the amount of cholesterol and fatty acids is observed. The anti-apoptotic and neurotrophic properties of ODN, including its anti-oxidant, anti-apoptotic and pro-differentiating effects, suggest that this gliopeptide and some of its selective and stable derivatives may have therapeutic value for the treatment of some neurodegenerative diseases.